PELATIHAN KIAT MENJADI PEMBELAJAR BAHASA INGGRIS YANG LEBIH BERHASIL BAGI SISWA SMA/SMK DI KOTA PALEMBANG - Ariya Agustin; M Bambang Purwanto (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2022)
English is an international language in Indonesia. It is important for students to master English because of its very central role in every aspect of this country. SMA and SMK students in Palembang City should prepare more seriously for their English language skills to face a better future. The English they study will have a very significant effect when they continue their education to tertiary level or enter the world of work. In this activity, the Darussalam Polytechnic lecturers, especially the lecturers for the English course, provided very important information for students in Palembang City to be successful in mastering English. This activity was carried out through a Zoom meeting with 40 participants consisting of high school and vocational students in Palembang City. This activity was carried out for 1 day on September 4 2022